Ilha de calor urbana: diagnóstico como ferramenta de gestão ambiental urbana para a cidade de Coari (AM) - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
Coari, a municipality located in the state of Amazonas, Northern Brazil, lies between the Solimões River and Lake Coari-Mamiá. Its climate is typically equatorial, characterized by two well-defined seasons: a hot summer and a rainy winter. The climate of the municipality is hot and humid, and the temperatures, for most of the year, provide perceptions of thermal discomfort. The design of horizontal gradients of temperature changes, i.e. higher temperatures in the centre relative to the periphery, becomes evident. This scenario arouses interest in investigating the local climatic behavior through a microclimatic assessment research. The study adopts a methodology based on the principles of Geographic Climatology and research on urban climate carried out in Brazil. This approach is divided into two phases: the first stage involves the collection and organization of data essential for the analysis, while the second phase focuses on processing this data for the purpose of mapping the heat islands in the urban area of Coari and identifying mitigation measures. Starting with a thorough mapping of the urban area, high-resolution satellite imagery is used to identify green areas, densely populated cores, suburbs, areas with exposed soil, and water bodies. Subsequently, images from the Landsat 8 satellite with a thermal infrared sensor are used to assess surface temperatures, providing better spatial resolution and discriminating temperatures in specific ranges. The identification of urban heat islands is based on the thermal difference between urban areas and their surroundings. Furthermore, the study investigates urban infrastructure in search of protected locations for the development of green areas, with the aim of mitigating the effects of heat islands. A special focus is directed to urban refrigeration technologies. The combination of these methodologies, covering geospatial, thermal and urban infrastructure analysis, aims to completely characterize Coari and identify effective strategies to reduce the impacts of heat islands, with the aim of improving the quality of life in the urban area.
Keywords: Ilha de calor urbana - Coari (AM); Climatologia urbana; Desenvolvimento urbano sustentável; ENGENHARIAS: ENGENHARIA DE PRODUCAO; ENGENHARIAS: ENGENHARIA DE PRODUCAO: ENGENHARIA DO PRODUTO: DESENVOLVIMENTO DE PRODUTO; Ilhas de calor; Microclimática; Conforto térmico; Infraestrutura urbana; Qualidade de vida